Hysterectomy and socioeconomic position in Rome, Italy. Issue 6 (1st June 2002) - Materia, E; Rossi, L; Spadea, T; Cacciani, L; Baglio, G; Cesaroni, G; Arcà, M; Perucci, C A
Abstract : Study objective: There exists conflicting evidence regarding the higher risk of hysterectomy among women of a lower educational and economic level. This study aims to assess whether in Italy socioeconomic level is related to hysterectomy undertaken for different medical reasons. Design: An area based index was used to assign socieconomic status (SES; four levels defined) to 3141 women (aged 35 years or older) who underwent a hysterectomy in 1997 and were residing in Rome. Data were taken from hospital discharge records. Direct age standardised hospitalisation rates by SES level were calculated for overall hysterectomies and for those performed for either malignant or non-malignant causes. Statistical differences were detected using the ratios of standardised rates and the test for linear trend. Main results: The hysterectomy rate was 36.7 per 10 000 women aged 35 years or more. Hysterectomy for uterine leiomyoma accounted for 41% of all operations and was more frequent among women aged 35–49 years than for those aged 50 years or more (crude rates: 28.6 and 7.7 per 10 000, respectively). The risk of hysterectomy was 35% higher for the lowest SES group, compared with the highest group. No association was found between SES and hysterectomy rates for malignant causes, although less affluent women in age group 35–49 years had 87% higher risk of hysterectomy compared with most affluent women. The inverse association between SES and hysterectomy rates attributable to non-malignant causes was statistically significant for women aged 35–49 years but not for those aged 50 years or more. Conclusions: The inverse relation between hysterectomy and SES is largely attributable to benign disorders of the uterus, namely leiomyoma and prolapse. More affluent women may have a greater uptake of less invasive techniques for removing uterine leiomyoma compared with less affluent women, who are more likely to undergo unnecessary hysterectomies irrespective of their reproductive age.